P14.77 Reduced dose craniospinal irradiation (CSI) is feasible for standard risk adult medulloblastoma (MBL) patients similarly to pediatric population. (6th September 2019) - Massimino, M; Sunyach, M; Gandola, L; Pecori, E; Spreafico, F; Bonneville Levard, A; Biassoni, V; Schiavello, E; Diletto, B; Stefini, R; Frappaz, D
Abstract: BACKGROUND: MBL is the most common malignant pediatric brain tumor but represents 1% of adult brain tumors. Recent molecular classification suggests that MBL is not the same disease in children and adults. For standard risk pediatric medulloblastomas current therapy includes CSI at reduced doses (23.4Gy) associated with chemotherapy. Most adult patients with similar risk factors still receive CSI at 36 Gy±chemotherapy (CT): in the adult series treated according to the HIT protocol (CSI 35.2 Gy + boost to 55.2 Gy to posterior fossa followed in most patients by maintenance CT with lomustine, vincristine and cisplatin) a 73% 5-year PFS was reported Friedrich, Eur J Cancer 2013, so far the best published data. Hence retrospective experience of 23.4 Gy together with CT for adult patients in some institutions is worthwhile reporting. MATERIAL AND METHODS: We gathered M0 patients, aged over 18 years with medulloblastomas and no/minimal post-surgical residues/no biological negative factor, between 1996–2018 in Centre Léon Bérard of-Lyon and Fondazione IRCCS Istituto Nazionale dei Tumori-Milan. RESULTS: Forty-four patients were included, median age 26 (18–48) years, 20 females. Median follow-up 90 months(10–227). Thirty-six and 8 received 23.4Gy and 30Gy CSI, respectively, + posterior fossa/tumor bed boost and CT in all: pre-RT (carbo/VPx2 courses or 8 drugs-in-one day x 2 courses (13 patients)) and/or post-RT (carbo/VPx2 courses in 11 and 8 drugs-in-one day x 2 courses in 10; CDDP/VCR/CCNU x 8courses in other 22). The 5/10 year PFS and OS were respectively 80.9±6.5%/76.8±7.4% and 88.4±5.5%/73.1±8.5%. Median progression time was 44 months. Relapses (8) were local (4), local+CSF or spine or bone in one instance each and bone only in one. Among variable considered, higher CSI dose than 23.4 Gy, pre-RT CT did not influence PFS, while females had a trend to better PFES and OS (P=0.07). CONCLUSION: These combined series present results comparable to - or even better than- those obtained after high CSI doses highlighting the need for treatment redefinition in adults.